Adapting And Resilient: How Indonesian Consumers Navigate E-Commerce Restrictions In The Post-Pandemic Retail Industry - Purnomo, Hery; M. Arfani; Shadiq, Teuku Fajar; Brumadyadisty, Garry; Asnawi, Anita (Journal of International Multidisciplinary Research, 2024)
This research aims to examine changes in consumer attitudes and purchasing power in the Indonesian market after the pandemic, with a focus on the impact of restrictions on online sales via social media. The COVID-19 pandemic has significantly changed consumer behavior, triggering a shift from conventional transactions to online platforms. However, online sales restrictions implemented by the Indonesian government raise questions about how consumers will respond and adapt to these changes. This research uses qualitative research methods, namely by describing systematically by conducting literature reviews about post-pandemic consumer behavior, and the impact of social media on purchasing decisions, surveys or questionnaires, and in-depth interviews with consumers to understand attitudes, and their experiences regarding online shopping on social media during the post-pandemic period. The research results reveal that restrictions on online sales via social media influence consumers' attitudes towards online shopping, forcing them to look for other alternatives or change purchasing preferences. Apart from that, these restrictions also have an impact on consumer purchasing power and consumption patterns. This analysis describes post-pandemic market dynamics in Indonesia, where e-commerce companies and business people have to adapt to changes in consumer behavior. Policy implications for the government and marketing strategies for business people are also discussed in the research providing an in-depth look at how to optimize market potential in Indonesia. amid restrictions on online sales. This research aids in comprehending the ongoing alterations in the Indonesian consumer market post-pandemic, thereby guiding government, companies, and other business entities in decision-making processes.